“EVERYTHING ABOUT US IS FEMINIST”: The Significance of Ideology in Organizational Change - Thomas, Jan E. (Gender & Society, 1999)
This study explores the role feminist ideology played in long-term structural changes in feminist organizations. The vehicle for this exploration was a comparative case study of 14 feminist women's health centers that were started in the 1970s and were still in existence in the early 1990s. Drawing on interviews and site visits, the author describes the early collectivist structures, highlights some of the crises these organizations faced, and describes three structural ideal types that emerged in the 1990s. The analysis suggests three ideological issues that directed structural change: the importance of maintaining a system for the equitable distribution of power, the importance of growth versus autonomy, and the importance of feminism as an organizational outcome or internal process.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem7000; justice sociale; militance; organisations féministes; pratiques féministes; périodes historiques; recherche participative; régions géographiques; sciences humaines; structures organisationnelles; thématiques; travail social; états-unis; étude de cas

L’approche féministe en termes de rapports sociaux ou l’art de survivre sur la corde raide en talons hauts! - Bourgon, Michèle (Service social, 1987)
Préoccupée d'une part par la situation des femmes qui, suite aux bouleversements provoqués par les luttes féministes, ont à vivre sous la pression de messages sociaux contradictoires, intéressée d'autre part par les pratiques sociales qui, dans le contexte actuel de transformations basées sur la rationalisation des budgets et des services, se trouvent confrontées à des visions divergentes quant à la nature et la fonction de l'intervention sociale, Pauteure expose et illustre une approche d'intervention féministe visant la défense des intérêts des femmes et la transformation des rapports sociaux dominants.
Keywords: approches et analyses; cours; discipline; discours dominant; histoire et politique; justice sociale; premier cycle; sciences humaines; systèmes d'oppressions; thématiques; travail social; trs1205